Seroprevalence of Trypanosoma evansi infection in capybaras (Hydrochoerus hydrochaeris) from a nonendemic area in Brazil - Da Silva A.S.* (2016)
© 2016, © 2016 The Author(s).In South America, capybaras (Hydrochoerus hydrochaeris) as well as coatis (Nasua nasua) are the reservoir hosts of Trypanosoma evansi. Capybaras from a T. evansi nonendemic area in the State of São Paulo, southeastern Brazil, were culled because of an ongoing outbreak of Brazilian spotted fever; serum samples from these capybaras were tested for antibodies to T. evansi. Of the 172 sera tested, 17 (9.9%) were seropositive by card agglutination test, with antibody titers of 1:8–1:128; 14 (8.1%) of these 17 seropositive sera were also seropositive by indirect fluorescent antibody test, with antibody titers of 1:16–1:256. Both serologic techniques proved to be efficient, with similar results for detection of antibodies to T. evansi in capybaras from a nonendemic area in Brazil.